Knowledge, Attitude and Practice of Contact Lens Users among South Indian Population - Shaik, Rahamthulla; Samanthula, Bala Sowmya; Pulivarthi, Sundara Karthik; Adusumilli, Pramod Kumar (Journal of Pharmacy Practice and Community Medicine)
Introduction: Despite the fact that usage of contact lens is increasing exponentially, users are unconscious about the after-exposure effects and complications arises due to unconventional usage. The main objective of the study is to evaluate the user’s knowledge, attitude, practice while using the contact lens and creating an awareness about their appropriate usage and possible complications of improper usage. Materials and Methods: In this cross-sectional study, a validated questionnaire was sent to the participants who used contact lens at least once in their lifetime for any reason. Out of 102 respondents, 100 gave consent to participate in our study and data was recorded and analyzed. Results: Out of 100, 69% of participants were females and 31% were males. Majority of the subjects were in the age group of 21 – 30. Only 50% of the participants were equipped with the knowledge of reporting product quality issues and 63% of users know the complications of usage. 9% used the contact lens upon conjunctivitis. 21% used the lens solution beyond 6 months and significant number of subjects (68%) preferred spectacles over lens. Absolute recommendation of contact lens was found among 26% of users and only 29% used the lens for refractive purpose. Conclusion: A better knowledge was observed in majority of contact lens users about usage complications and a very few suggested contact lenses to non-users; this indicates that users are uncomfortable while using contact lens. Providing necessary training on proper usage and reporting of contact lens related adverse events to the regulatory authority shall ensure quality of the lenses marketed in India and safety of the users.
Keywords: Acanthamoeba infection; Microbial Keratitis; Contact lens; Conjunctivitis; Questionnaire; Cross-sectional study.